Isu Urutan Dua Vokal di Sempadan Awalan: Satu Penjelasan Analisis Spektrografik (Jurnal Bahasa, 2012)
This paper examines two-vowel sequence, a common topic of discussion among Malaysian linguists. Opinions differ as to whether there is a glottal stop sound especially at the boundary of the prefix. Some experts mention the presence of a glottal stop sound while others mention that the sound of the vowel sequence becomes a glide. Hence, this study makes use of spectrographic analysis to explain this issue by identifying the acoustic characteristics which exist at this boundary. Several sample vowel sequences, representing selected words, were recorded from 32 Malay youths and adults. These recordings were then converted into a spectrogram data and analyzed. The study found that the acoustic characteristic of the glottal stop sound were only found in the adults recorded data while the acoustic characteristic of the "glide" were found in the youths'. The study reveals numerous acoustic characteristics related to different genders and different age groups.Keywords: prefix, spectrogram, spectrographic analysis, acoustic